Fuel-to-air ratio control under short-circuit conditions through UEGO sensor signal analysis. (November 2020) - Guardiola, Carlos; Pla, Benjamín; Real, Marcelo; Travaillard, Cyril; Dambricourt, Frederic
The impact of short-circuit pulses on the after-treatment system of a spark-ignited engine must be taken into account to keep the fuel-to-air equivalence ratio within the three-way catalyst window, thereby reducing pollutant emissions. The fuel-to-air equivalence ratio overestimation that suffers the wide-range λ -sensor upstream three-way catalyst in the presence of short circuit is especially relevant. In this study, a novel approach to deal with the fuel-to-air equivalence ratio control under short-circuit conditions is introduced. Under this scope, this work proposes a strategy for the on-board correction of the aforementioned fuel-to-air equivalence ratio overestimation, by means of the information regarding short-circuit level that provides the frequency content of the λ -sensor at the engine frequency. Finally, the potential of this approach to minimize pollutant emissions, in particular the NO x penalty arisen as a consequence of running the engine under leaner conditions than expected, is assessed through experimental tests.